EKSISTENSI SUBAK DI BALI: MAMPUKAH BERTAHAN MENGHADAPAI BERBAGAI TANTANGAN - SUTAWAN, NYOMAN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 1, No. 2 Juli 2001)
This paper discusses the present and future challenges faced by the Balinese subak. Those challenges are: increasing competition in the marketing of agricultural products due to the trade liberalization; the declining interest of the rural youth to work as farmers; financial burden of the farmers due to irrigation management transfer and payment of irrigation service fee; the decline of irrigated land areas due to the conversion for other uses; degradation of environment; and limited availability of water resources. It is argued that subak has strengths and therefore may be able to cope with such challenges because subak is indeed a viable institution as indicated by the fact that it has been in existence for many centuries. However, subak also has some weaknesses. It is necessary therefore, that some efforts need to be done to empower subak so that it can survive to cope with those challenges.
Keywords: Challenges, Subak’s strengths, and weaknesses, Subak empowerment.